SPEECH CULTURE AND LANGUAGE PURITY (American Journal of Pedagogical and Educational Research, 2023)
This article is aimed at consideration of issues concerning the speech culture in everyday life. The issues of violating the main principles of business relations ethicality during public speaking and deviation from the language norms have been considered. Besides, the conclusions as to formal speech peculiarities have been made. The article covers the public speaking stages, methods of due speech formation, preparation for meeting the listeners and techniques to control the audience. The explanations related to the courtly use of speech tokens according to the ethic standards and the ways to improve the ones, which express the respectful attitude towards listeners, have been given.